Performance of a hybrid fine pitch quad flat package mounted with a new flux on printed circuit board in surface insulation resistance test. Issue 10 (16th October 2020) - Zhou, D.; Haseeb, A.S.M.A.; Andriyana, A.; Wong, Y.H.; Sabri, M.F.M.; Low, B.Y.; Pang, X.S.; Eu, P.L.; Tan, L.C.
Abstract: An innovative hybrid quad flat package is designed recently by incorporating two types of leads with two distinctive shapes: gull wing and J‐lead. These leads are separated into two layers to increase the adjacent space between them. Pure tin is used as the connector finish in the package, while Sn‐3.0 Ag‐0.5Cu solder material with a new flux is printed on the footprint copper pads of printed circuit board to join the hybrid packages on it. As compared to the conventional quad flat package, the design significantly increases the lead count by 50 % and reduces the distance between two types of leads to 0.325 mm, consequently improving the functional capability in a smaller size product. Surface insulation resistance test is conducted according to IPC‐TM‐650 standard to analyse the reliability of the newly designed hybrid quad flat package. The absence of tin whisker and dendrite after the test demonstrates the reliability of this hybrid package product and the new flux applied. Abstract : Surface insulation resistance test was conducted according to IPC‐TM‐650 standard to analyse the reliability of a newly designed hybrid quad flat package. After the test, the absence of tin whisker and dendrite in J‐lead and gull wing demonstrated the reliability of this hybrid package product and the new flux applied. Translation abstract: Eine innovative, rechteckige hybride Flachbaugruppe, die zwei unterschiedliche Pintypen, gull wing und J‐Lead, kombiniert, wurde entworfen. Diese Pins sind über zwei Schichten verteilt, damit der Pinabstand vergrößert wird. Auf der Oberfläche des Steckverbinders wird reines Zinn verwendet. Auf den Kupferpads der Leiterplatte wurde ein Sn‐3.0 Ag‐0.5Cu‐Lot mit einem neuen Flussmittel benutzt, um die gemischten Pakete zu verbinden. Dieses Design erhöht die Anzahl der Pins um 50 %, im Vergleich zu einer herkömmlichen, rechteckigen Flachbaugruppe, weil der Pinabstand auf 0, 325 mm reduziert wird. Dies verbessert somit die Funktionsfähigkeit eines kleineren Produkts. Der Oberflächenisolationswiderstand ist dem IPC‐TM‐650‐Standard gemäß getestet, um die Zuverlässigkeit der neuen Flachbaugruppe zu analysieren. Nach dem Testen war es frei von Zinnwhiskern und Dendriten, womit die Zuverlässigkeit dieses Hybridverpackungsprodukts und des neuen Flussmittels gezeigt wurde.